A Critique Of Ibn Al-Jawzi’s Discourse On Some Sufi Themes In His Talibisu Iblis - Gambari, Yusuph Dauda; Fatiu, Karatu (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Sufism is shrouded with many polemics which keep thickened by the day. The gap between the anti and pro-Sufi scholars continues to widen with time. As the former scholars intensified efforts to discredit Sufism, the latter strengthened moves to consolidate it in Islam. One of the scholars both sides relied on in their discussions is Ibn Al-Jawzī. Talbīs Iblīs, which forms the kernel of discussions in this paper, is one of his works on Sufism. It is often said that the work is an attack on Sufism, but the Sufis denied this, stating that it is just an appraisal of different groups that make up Islam. The effort here is to critique various mystical themes in the work vis-à-vis Sufis’ renditions to determine their level of correlation or otherwise. Historical and exegetical methods are adopted. The former availed the opportunity to dig into relevant historical facts, while the latter assisted in analyzing his submissions on Sufism. It is discovered that Ibn Al-Jawzī was not particular about Sufism, but all groups of Muslims identified how Iblīs deluded each. Also, he did not entirely condemn Sufism but considered some doctrines and practices strange therein. His submissions were guided by his little practice of Sufism and observations of Sufis of his time. The paper concluded that Ibn Al-Jawzī's effort is not different from Ahmad Ibn Hanbalī's among his precursors and Ibn Taymiyyah among his successors. Keywords: cAqīdah, Iblīs, Ibn Al-Jawzī, Sufism, Raqṣ, Zuhd